Asymptotically single-mode small-core terahertz Bragg fibre with low loss and low dispersion. (29th December 2016) - Hong, B; Swithenbank, M; Somjit, N; Cunningham, J; Robertson, I
Abstract: This paper presents a novel design concept, which is verified by analytical and simulation results, of a single-mode small-core terahertz Bragg fibre exhibiting the properties of low loss and low dispersion. Conventionally, a single-TE01 -mode Bragg fibre requires a large core and many cladding layer periods to achieve a significant propagation loss discrimination between the desired mode and other unwanted competing modes. The use of a second-order bandgap in this paper completely eliminates this requirement, and enhances propagation loss discrimination using just a small core with a diameter at least 50% smaller than the conventional design and only four cladding layer periods. Furthermore, a generalized half-wavelength condition is proposed, promoting the manipulation of photonic bandgap for Bragg fibre. The TE01 mode has a null point in the electric field close to the boundary interface between the core and the cladding, and this phenomenon has been exploited to minimize the impact of support bridges, which mechanically maintain the air gaps, on the propagation loss of the fibre. Finally, we propose a novel design of a tightly confined single-TE01 -mode small-air-core Bragg fibre with propagation loss and group velocity dispersion less than 1.2 dB m −1 and  −0.6 ps/THz/cm, respectively, between frequencies of 0.85 THz and 1.15 THz.